CHANGES IN CYTOKINES LEVELS IN ASTHMA PATIENTS WITH FREQUENT EXACERBATIONS - Dao, Ngoc Bang; Ta, Ba Thang; Nguyen, Huy Luc; Pham, Dac The (Tạp chí Y Dược học Quân sự (Vietnamese issues), 2024)
Objectives: To evaluate changes in serum levels of some cytokines in asthma patients with frequent exacerbations. Methods: A prospective, descriptive, longitudinal study on 60 asthma patients with frequent exacerbations and 60 ones with few exacerbations, treated as outpatients at the Asthma Management Department, Hai Phong International Hospital from January 2020 to May 2023. Patients underwent clinical examination, chest X-ray, respiratory function test, and assessment of inflammatory markers and serum cytokine levels at the time of the study. Results: The asthma group with frequent exacerbations had significantly higher IL-4 and IL-13 concentrations than the asthma group with few exacerbations (21.10 and 9.93 pg/mL vs. 16.48 and 3.95 pg/mL). Concentrations of IFN-α, IFN-γ, IL-17, and inflammatory cytokines (IL-12, TNF-α, IL-1β) were not different between the 2 asthma groups. In the asthma group with frequent exacerbations, most serum cytokine concentrations in male patients were insignificantly higher than in females, except for IL-12. IL-17, IFN-α, IL-4, and IL-12 concentrations in patients aged ≥ 60 years were insignificantly higher than those in the group < 60 years old. Conclusion: There are significantly higher serum levels of IL-4 and IL-13 in asthma patients with frequent exacerbations compared to those with few exacerbations.